PENERAPAN TEKNIK BRAINSTORMING TERHADAP KEMAMPUAN MENGAPRESIASI PUISI SISWA KELAS VI SD INPRES LAPPARA KECAMATAN TOMBOLO PAO KABUPATEN GOWA - Baharuddin Baharuddin (JURNAL KONFIKS, 2017)
The purpose of this classroom action research is to know the ability of students to appreciate poetry through brainstorming technique which is expected to improve the process and the result of learning Indonesian especially poetry appreciation in grade 6 students of Inpres Lappara Elementary School with the number of subject as many as 24 people. The technique used in this research is a qualitative description. The class action research plan is implemented in two cycles. Each cycle has four stages: planning, implementation, observation, and reflection.The results of this class action research indicate that: (1) there is a positive change of activity in each cycle. (2) the average score increased according to the criteria: (theme 65 in cycle I increased to 68.83 in cycle II, 65.69 increase to 68.83, 66.63 note increased to 73.96, and mandate 67 , 79 increased to 72.54); (3) the average percentage of the ability to appreciate the increased poetry is related to the minimum completeness criterion that is small value of 65 (52,09% in cycle I decrease to 12,50%) and big value from 65 (47,915% increase to 87,50% ) shows a significant result.In accordance with the results of this PTK expressed significantly increased. Therefore, to grade 6 teachers of Inpres Lappara Elementary School, Tombolo Pao, Gowa District is expected to apply brainstorming technique to Indonesian language learning especially poetry appreciation.